Communist Ideological Imprinting and the Transformation of State‐owned Enterprises. (26th June 2022) - Zhang, Liang; Ren, Yeyao; Wu, Jianzu
Abstract: Despite an increasingly similar institutional environment for state‐owned enterprises (SOEs), some SOEs adapt to transformation more rapidly than others. We seek answers to this puzzle by examining how founding institutional environments shape the timing of SOE transformation. We first employ imprinting theory to argue that SOEs founded in different environments are imprinted with different political ideologies that influence their subsequent transformation timing. Using a dataset from the Annual Census of Chinese Industrial Enterprises from 1998 to 2007, we find that SOEs' communist ideological imprint negatively affects their faster transformation. Drawing on insights from institutional theory, we also consider the contextual factors that influence the strength and decay of the imprint. We find that SOEs affiliated with central government at founding develop a stronger imprint, but mimetic force and regional marketization in the current environment weaken the negative effect of the imprint on faster SOE transformation. We discuss the contributions to the literature on SOE transformation and imprinting and the research at the intersection of imprinting and institutional theory.